MENINGKATKAN ANTUSIASME SISWA TERHADAP KEGIATAN BELAJAR DAN PEMBELAJARAN DI KELAS MELALUI PROGRAM LITERASI MEMBACA â€œTUNGGU AKUâ€ - Suciati, Titik (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Reading Literacy Program "Tunggu Aku" conducted at MI Diponegoro 03 Karangklesem can increase students' enthusiasm in studying and learning in the classroom. From the three activities there was a collaboration between the teacher and guardians of the students to make this program successful. There are three activities in this literacy program that are reading activities, and pre-reading activities carried out with parents at home, as well as post-reading activities that will be carried out with the teacher at the school. Of the three activities above, the teacher uses post-reading activities to maximize this reading literacy program, which is to increase students' enthusiasm in studying and learning in the classroom. Post-reading activities conducted by teachers and students include: (1) developing imaginative thinking skills through storytelling; (2) developing students' thinking skills by playing word concept maps; and (3) developing children's thinking skills through playing letter patterns in words. Keyword: Antusiasme Siswa, Kegiatan Belajar, Pembelajaran, Dan Literasi Membaca